INCREMENTAL CAPITAL OUTPUT RATIO : EFISIENSI INVESTASI PEREKONOMIAN KABUPATEN/KOTA DI SUMATERA UTARA - Gurning, Masta Juwita; Bangun, Rita Herawaty (Universitas Halu Oleo, 2020)
The purpose of the research is to look at investment and economic growth in regency/city throughout North Sumatra through the ICOR value calculation method during the period 2014 - 2018. This research uses descriptive analysis techniques using secondary data. The results also show there is still a disparity in investment growth between regions in North Sumatra. The highest investment percentage is in the city of Medan. This is influenced by the factor of the city of Medan as the provincial capital which is the center of all economic activity in North Sumatra and seen investment has increased from time to time. The lowest percentage occurred in Samosir regency, meaning that in Samosir district there was a slowdown in investment growth. To further increase investment and reduce disparities between regions, local governments should be able to take rare, accurate measures to improve this situation so that high economic growth and efficiency in investment management can be achieved. Therefore, in setting the target of economic growth rate, the local government should calculate the amount of ICOR in order to estimate the amount of investment needs to achieve the growth target set in the future.